The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1590/s0100-69912000000600008
|View full text |Cite
|
Sign up to set email alerts
|

Trauma torácico: fatores de risco de complicações pleuropulmonares pós-drenagem pleural fechada

Abstract: O objetivo do presente estudo foi avaliar a importância dos fatores de risco na gênese das complicações pleuropulmonares, pós-drenagem pleural fechada. Analisou-se, prospectivamente, no período de janeiro de 1998 a junho de 1999, um total de 167 pacientes submetidos à drenagem pleural fechada, sendo estratificados em dois grupos selecionados para um estudo de acompanhamento de coortes. Ao grupo controle, de 104 pacientes, não foi administrada antibioticoterapia e, no grupo experimental, de 63 pacientes, a cefa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
1
9
0
2
Order By: Relevance
“…The literature tends to high quote the penetrating mechanism as a risk factor for empyema, but this is controversial and the reasons are not objectively clarified 3,4,12,16 . Another study in Brazil has found similar results to this work regarding the incidence of empyema according to the mechanism of trauma 19 . In this work, the finding may be explained by the patient's age effect, once among the 33 patients with penetrating trauma by firearms, only two were older than 40 years (6%), as opposed to 13 among the remaining 28 with penetrating trauma by knife or blunt trauma (46.4%) (data not shown).…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The literature tends to high quote the penetrating mechanism as a risk factor for empyema, but this is controversial and the reasons are not objectively clarified 3,4,12,16 . Another study in Brazil has found similar results to this work regarding the incidence of empyema according to the mechanism of trauma 19 . In this work, the finding may be explained by the patient's age effect, once among the 33 patients with penetrating trauma by firearms, only two were older than 40 years (6%), as opposed to 13 among the remaining 28 with penetrating trauma by knife or blunt trauma (46.4%) (data not shown).…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 88%
“…In this work the incidence was 32.8%, 16.4%, and 4.9% for empyema, pneumonia and infected pulmonary contusion, respectively. Empyema demands surgical treatment in some cases, being one intrathoracic complication with serious damage for patients 19 . Patients with penetrating trauma by firearms had significantly lower risk of empyema compared to those with penetrating trauma with knives and blunt trauma.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
See 3 more Smart Citations